Fluorine Modification over Activated Carbon Electrodes Enabling Stable 3 V Supercapacitor Operation. Issue 1 (June 2021) - Wu, X; Bai, Y; Yang, C; Li, H; Chen, W; Han, X
Abstract: High-energy-density electrochemical supercapacitors are required by various fields in modern society. Low-temperature plasma technology is used to produce fluorine-containing functional groups on the surface of the activated carbon electrode in CF4 gas. The passivation layer formed by the fluorine element on the electrode surface can effectively prevent the electrode material from reacting with the electrolyte, which leads to the breakdown of the electrolyte during the charging and discharging process of the supercapacitor and the destruction of the electrode material structure. After 12, 000 charge-discharge cycles at 3 V, the capacitance retention rate of supercapacitors modified by fluorine for 9 minutes is 91.81%, which is 30.95% higher than that of the control group. In addition, the specific capacitance of the electrode has also increased to a certain extent.